Problem-Based Educational Games for Pancasila Education: Enhancing Elementary Students’ Learning Outcomes through Interactive Digital Media - Aprima; Ketut Agustini; I Gde Wawan Sudatha (Universitas Pendidikan Ganesha, 2026)
Pancasila Education in elementary schools often faces challenges related to textual content, limited media variation, and low student engagement. This study aimed to develop and examine the effectiveness of a problem-based educational game as an interactive digital medium for improving fourth-grade students’ learning outcomes in Pancasila Education. The study employed a research and development design using the Multimedia Development Life Cycle model, which consisted of concept, design, material collecting, assembly, testing, and distribution stages. The participants included fourth-grade students and teachers at SDN 4 Pangkalanbaru, along with content experts and media-design experts involved in product validation. Data were collected through observation, interviews, questionnaires, expert validation sheets, student and teacher response questionnaires, and pretest–posttest learning outcome tests. The results showed that the educational game obtained a Gregory validity score of 1.00 for both content and media-design aspects, indicating very high validity. User trials also produced positive responses, with 91.11% in individual testing, 91.26% in small group testing, and 88.21% in field testing. The effectiveness test showed that students’ mean score increased from 53.75 to 87.71, with a significance value of 0.001 and an N-Gain score of 0.734. These findings indicate that problem-based educational games are valid, practical, and effective for supporting interactive Pancasila Education learning.